Public communication in two rural Kansas communities: a rhetorical analysis of local government messaging - Smith, Cy Jacob (My University, 2024)
This study investigates the communication strategies employed by local government officials in two rural Kansas communities to foster development and build trust with constituents. Rural America faces unique challenges, including population decline and economic disadvantages (Radin, 2022). Effective communication is crucial for addressing these issues and promoting sustainable development. The research examines two rural Kansas communities, comparing the communication patterns of their local governments. It explores the role of government messaging in addressing community development, collaboration, and resources. Using three different frameworks that address time and tone, community capitals, and communication roles, this study provides an analysis of social media and news releases from local governments in McPherson and Montgomery County, Kansas. McPherson County has a high score on the Community Health Rankings index, while Montgomery County has a low score. To better understand the differences in communication patterns in the two counties, a content analysis was performed. By understanding the dynamics of communication in these two communities, this research provides valuable insights into how local government messaging supports community development efforts. Results show that there are both similarities and differences between the two communities’ public communication, despite drastically different County Health Rankings. This study contributes to the literature surrounding rural community development, and to the literature on public communication, especially as it relates to local governments in Kansas.
Keywords: Community development; Rhetoric; Local government; Public communication